2010
DOI: 10.1111/j.1751-553x.2009.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicovirologic analysis of hepatitis C infection in transfusion‐dependent β‐thalassemia major children

Abstract: Regular blood transfusion puts beta-thalassemia major patients at a higher risk of developing hepatic iron overload and hepatitis C virus (HCV) infection. The association between several transfusion-related factors and an increased risk of developing HCV viremia has been reported. The effect of HCV infection on liver damage in transfusion-dependent thalassemia patients has been poorly described. A sample of 100 Egyptian transfusion-dependent beta-thalassemia major children were studied. Individual patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This observation is differs from our results, and the discrepancy may possibly be due to the difference in prevalence of these infections in the donating blood pool population as patients from countries highly endemic for HBV are more likely to develop occult HBV infections [21]. Our results showed an increased prevalence of occult HBV infection in patients older than six years of age, who have had a higher number of blood transfusions than younger patients, and these observations are similar to those of many other reports [9,4,14]. In our study, the majority of the patients were males, representing 67.4% of the subjects, which is similar to observations of male preponderance in such infections in other investigations [7,4].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This observation is differs from our results, and the discrepancy may possibly be due to the difference in prevalence of these infections in the donating blood pool population as patients from countries highly endemic for HBV are more likely to develop occult HBV infections [21]. Our results showed an increased prevalence of occult HBV infection in patients older than six years of age, who have had a higher number of blood transfusions than younger patients, and these observations are similar to those of many other reports [9,4,14]. In our study, the majority of the patients were males, representing 67.4% of the subjects, which is similar to observations of male preponderance in such infections in other investigations [7,4].…”
Section: Discussionsupporting
confidence: 82%
“…A recently published study on Egyptian transfusion-dependent beta-thalassemia major children showed that HCV-PCR in liver biopsy was positive in 64% of patients [14]. Others reported 45% of their thalassemia patients positive for HCV-RNA [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV infected patients had significantly higher enzymes than non-infected 13. chronic hepatitis C virus infection has been associated with liver iron loading.…”
Section: Introductionmentioning
confidence: 93%
“…Life-long transfusion regimens are essential to alleviate anaemia. Although regular blood transfusions have largely improved the prognosis, iron overload, especially in the liver (liver siderosis), and high risk of hepatitis C infections constitute a real threat to the quality of life of beta-thalassemia patients [19]. In beta-thalassemia patients both iron overload and HCV-related liver disease lead, albeit through different mechanisms, to hepatocellular necrosis, fibrosis, and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%